Analyzing the coupling coordination between aviation logistics and the regional economy: Identifying coupling mechanisms and critical influencing factors - Lijun Liang; Peirong Chen; Mengwan Zhang (PLoS ONE, 2025)
The relationship between aviation logistics and the regional economy (AL&RE) is mutually reinforcing. This study aims to develop a research framework for evaluating the coupling coordination level and identifying critical influencing factors in regional AL&RE by integrating the coupling coordination degree model with grey relational analysis. The framework is designed to guide regional policy formulation, fostering economic development through the coordinated advancement of AL&RE. To validate its effectiveness, an empirical analysis is conducted using data from Sichuan Province in China for the period 2013–2023. The key findings are as follows: (1) In Sichuan Province, local government expenditures on civil aviation development funds play a crucial role in supporting aviation logistics, while GDP and the proportion of investment in environmental pollution control relative to GDP significantly impact the regional economy. (2) The coupling degree between AL&RE remains high, with coordination generally improving, although occasional declines occur due to internal imbalances caused by external factors. (3) The influence of each indicator on coupling coordination varies, with civil aviation cargo turnover, throughput, and civil aviation take-off and landing sorties being the most significant. (4) Critical factors influencing AL&RE development differ from those affecting their coupling coordination, underscoring the nonlinear nature of this composite system. The study theoretically constructs a composite system for AL&RE and analyzes their coupling mechanism, addressing a significant research gap. It also integrates green indicators into the regional economic subsystem, offering a novel perspective for future research. Practically, the study provides recommendations for enhancing AL&RE coordination in Sichuan.